Combined high-throughput and fractionation approaches reveal changes of polysaccharides in blueberry skin cell walls during fermentation for wine production. (December 2022) - Zhang, Nawei; Gao, Yu; Fan, Gang; Zhong, Wu; Chen, Xuanxuan; Guo, Xiao; Hansen, Jeanett; Jørgensen, Bodil; Li, Erhu
Graphical abstract: Highlights: Cell wall profiling was applied throughout the winemaking process. Fractionation techniques with CoMPP elucidated blueberry skin deconstruction. Blueberry skin cell wall is rich in xyloglucan. The enzyme-resistant pectin polymers were tightly bound to hemicellulose. Abstract: There have been rare reports about the structure/composition of polymers in blueberry skin and their changes during fermentation for wine production. In this study, the compositional changes occurring in blueberry skin during fermentation were tracked by a combination of cell wall analysis techniques including infra-red spectroscopy, monosaccharide analysis, and comprehensive microarray polymer profiling (CoMPP). The cross-corroborating data revealed that blueberry skin cell wall is particularly rich in xyloglucan. Chemical fractionation analysis indicated that the KOH soluble fraction is a dominant fraction in fermented blueberry skin. Interestingly, the KOH soluble fraction contained abundant epitopes associated with pectin branch chains, indicating tight binding of some enzyme-resistant pectin polymers to hemicellulose. This study provides important implications for the development of effective strategies to extract beneficial substances (such as aromatics, tannins and pigments) from berry tissues during processing.